Chemical Approaches toward Graphene-Based Nanomaterials and their Applications in Energy-Related Areas - Luo, B.; Liu, Shaomin; Zhi, L. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
A ‘gold rush’ has been triggered all over the world for exploiting the possible applications of graphene-based nanomaterials. For this purpose, two important problems have to be solved; one is the preparation of graphene-based nanomaterials with well-defined structures, and the other is the controllable fabrication of these materials into functional devices. This review gives a brief overview of the recent research concerning chemical and thermal approaches toward the production of well-defined graphene-based nanomaterials and their applications in energy-related areas, including solar cells, lithium ion secondary batteries, supercapacitors, and catalysis.